Beyond effectiveness evaluation: Contributing to the discussion on complexity of digital health interventions with examples from cancer care - Ventura, Filipa; Brovall, Maria; Smith, Frida (Frontiers in Public Health, 2022)
Digital health interventions (DHI) have become essential complementary solutions in cancer care to enhance support and communication at the distance between treatment sessions, with evidence of improving patient outcomes. Impacting clinical outcomes is a major determinant of success in any health intervention, influencing its funding, development, adoption and implementation in real-world practice. However, DHI comprise many complexity elements that lead to uncertainties in terms of determining intervention’s effectiveness. In this article, we aim to contribute to the current paradigm change in effectiveness assessment of DHI. We depart from the experiences of developing and testing three DHI to discuss the complexity elements concerning effectiveness assessment. Underpinned on the complexity theory endorsed by the Medical Research Council framework (MRCf) and the Non-adoption, Abandonment, Scale-up, Spread and Sustainability framework (NASSSf), we identify challenges in the research lifecycle of DHI. The methodological discussion of the identified challenges endorses the need of adopting research designs that enable the combination of mixed-methods to gather the different stakeholder and end-users perspectives, and timely evaluation approaches that value effectiveness outcomes as much as process outcomes, anchored on clinical practice. Furthermore, the dissemination and sustainability agenda of DHI needs to be considered from early-stage development with the inclusion of a business model that assures the management and maintenance of the DHI throughout time in partnership with healthcare services, regulation bodies and industry.